DOI: 10.31274/rtd-180813-13570
|View full text |Cite
|
Sign up to set email alerts
|

Low bandgap α-(Si,Ge):H and α-(Ge):H devices

Abstract: This manuscript has been reproduced from the microrilm master. UMI films the text directly from the original or copy submitted. Thus, some thesis arxJ dissertation copies are in typewriter face, while others may t>e from any type of computer printer. The quality off this rBproduction is dependent upon the quality of the copy submitted. Broken or indistinct print, colored or poor quality illustrations and photographs, print bleedthrough, substandard margins, and improper alignment can adversely affect reproduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
66
0

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(69 citation statements)
references
References 28 publications
3
66
0
Order By: Relevance
“…Other parameters, which can influence the loading of DOX on GO, are the initial concentration of DOX and the contact time of DOX with GO. The more primary concentration of DOX leads to more loading on GO in a linear pattern [10,[17][18][19][20][21]. Nevertheless, Wu et al indicated that DOX dosage greater than 0.5 g/L leads to less loading of DOX on GO because of DOX accumulation and a decrease in the number of active sites.…”
Section: Introductionmentioning
confidence: 99%
“…Other parameters, which can influence the loading of DOX on GO, are the initial concentration of DOX and the contact time of DOX with GO. The more primary concentration of DOX leads to more loading on GO in a linear pattern [10,[17][18][19][20][21]. Nevertheless, Wu et al indicated that DOX dosage greater than 0.5 g/L leads to less loading of DOX on GO because of DOX accumulation and a decrease in the number of active sites.…”
Section: Introductionmentioning
confidence: 99%
“…Probably, the shared active sites formed between the heterodimeric subunits of the same branch are structurally similar to those of the corresponding homodimers. All of them are characterized by seven conservative regions denoted in Figure 1 as R1-R7, which comprise the following residues (according to LE-ACS2): R1 (49)(50)(51)(52)(53)(54)(55)(56)(57)(58), R2 (89)(90)(91)(92)(93)(94)(95)(96)(97), R3 (136)(137)(138)(139)(140)(141)(142), R4 (205)(206)(207)(208)(209)(210)(211)(212)(213), R5 (274-288), R6 (304-311), and R7 (407-417). 51 The inactivity of certain heterodimers is probably due to structural restraint(s) that prevents the shared active sites to be functional.…”
Section: Inhibitors Of the Catalytical Activity Of Acsmentioning
confidence: 99%
“…An exception to this rule is ACS7, which is able to form functional heterodimers with some members of both branches. 26,28,29,33,45,46,48,51,[56][57][58][59] The localization of these residues is illustrated in Figure 1 and all of them are numbered according to LE-ACS2 (in parentheses the equivalent amino acid residue in Md-ACS1) and are characterized as follows: If indeed ACS heterodimers are formed in plants, they could provide an additional regulatory element in ethylene production.…”
Section: Inhibitors Of the Catalytical Activity Of Acsmentioning
confidence: 99%
“…High performance liquid chromatography (HPLC) is one of the most useful techniques for the quantification of some of the four compounds [2][3][4][5][6][7], but the use of HPLC is restricted by long analysis times, peak asymmetry and poor efficiency [6,7]. Proton nuclear magnetic resonance (NMR) [8] and gas liquid chromatography [9] have also been reported for the determination some of these analytes.…”
Section: Introductionmentioning
confidence: 99%